Communication skills in tourism studies curricula in Slovenia: The case of the Slovene language skills of tourism students - Potočnik-Topler Jasna (University Educons, Faculty of Sports and Tourism, Novi Sad, 2017)
This paper examines communication skills of tourism students in Slovenia. Besides rhetoric skills and speaking foreign languages, for tourism students, mastering their mother language is significant. The survey has shown that the students of tourism enrolled at the Faculty of Tourism of the University of Maribor are not systematically trained in their mother language skills at the university level. Consequently, during oral exams and their oral presentations tourism students display strong traces of their dialects, and they make pronunciation mistakes. The most common students' mistakes are the following: incorrect pronunciation of some proper names, pronouncing the wrong syllable, and the incorrect pronunciation of the Slovene participles.